2016
DOI: 10.5812/thrita.36365
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Psychiatric Disorders in Methadone Maintenance Therapy (MMT) Clients

Abstract: Background: Methadone maintenance therapy (MMT) is currently widely accepted as the treatment of choice for opioid replacement therapy. Objectives: The aim of this study was to determine the prevalence of HBV, HCV, and HIV infections as well as psychiatric disorders in our MMT cases. Patients and Methods: Using a cross-sectional study design, we studied patients treated for opioid abuse or addiction who attended MMT programs in Rafsanjan, Iran, from March to June 2012. HIV, HBV, and HCV test reports were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…So, gut microbial diversity might be shaped by addiction-associated behaviors and these can function as biological indicators to evaluate the health of people with a history of drug use. Also, disturbances in mental health parameters and metabolic profiles have previously been documented in opioid users and patients receiving MMTPs [ 7 , 44 ]. This evidence suggested a potential link involving the gut microbiota, metabolism, and psychological factors that warrant consideration therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“…So, gut microbial diversity might be shaped by addiction-associated behaviors and these can function as biological indicators to evaluate the health of people with a history of drug use. Also, disturbances in mental health parameters and metabolic profiles have previously been documented in opioid users and patients receiving MMTPs [ 7 , 44 ]. This evidence suggested a potential link involving the gut microbiota, metabolism, and psychological factors that warrant consideration therapeutically.…”
Section: Discussionmentioning
confidence: 99%
“…We read an interesting article by Abousaidi et al recently published in Thrita Journal in which they found 1.7% hepatitis C virus (HCV) infected patients among their study participants (1).…”
Section: Dear Editormentioning
confidence: 99%